The Indian Database Scenario Portrayed Through INDAB - Sur, S.N.; Singh, Sunder (DESIDOC Journal of Library & Information Technology, 2002)
There is a marked shift from predominantly library based bibliographic information services to the generation of more factual, referral, numeric and multimedia information products. yet, comparing with the global developments, we, the Indians are just at the starting line. In this article, portrayed through INDAB the indigenous database efforts, their growth & status, availability, opportunities for development, and related strategies have been analysed. It concludes that given some areas of strength and planned growth, India should have increased opportunities in information services in the years to come. http://dx.doi.org/10.14429/dbit.17.5.3231